Pengaruh Kecemasan Dan Conscientiousness Terhadap Keputusan Penggunaan Kontrasepsi Pada Wanita Usia Subur - Rochmawati; Hera Lestari Mikarsa; Ira Puspitawati (Universitas Darul Ulum, 2025)
Decision making in contraceptive use is influenced by various psychological factors, including anxiety about the negative effects of contraception and individual personality characteristics. This study aims to analyze the effect of anxiety about the negative effects of contraception and the personality dimension of conscientiousness on decision making in contraceptive use in women of childbearing age. The method used in this study is multiple linear regression involving 120 respondents of childbearing age women. Variable measurements were carried out using the Decision Conflict Scale, Generalized Anxiety Disorder-7 (GAD-7), and the conscientiousness dimension of the Big Five Inventory (BFI). The results of the analysis showed that anxiety about the negative effects of contraception had a negative and significant effect on decision making (β = -0.520, p <0.001), while conscientiousness had a positive and significant effect on decision making (β = 0.763, p <0.001). The regression model has an Adjusted R² value of 0.378, which indicates that 37.8% of the variability in contraceptive use decisions can be explained by these two variables. These findings emphasize the importance of managing anxiety and increasing individual awareness in decision-making regarding contraception in order to improve reproductive well-being.